CHANGE OF DURATION OF VEGETATION PERIOD AND PHASES OF GROWTH AND DEVELOPMENT OF SOYBEAN PLANTS DEPENDING ON GROWING CONDITIONS - Міленко, О. Г. (Scientific Progress & Innovations, 2015)
Influence of weather conditions, variety properties of varieties, different methods of crops’ care and seeding rate on duration of vegetation period and phases of growth and development of soybean plants has been established. Weather conditions of the year most influenced on vegetation period and separate phases of growth and development of soybean plants. There was considerable shortening of vegetation period of soybean plants in droughty years. The method of crops care not substantially influenced on soybean plants’ organogenesis. Sagement of agrophytocenosis affected phases of growth and development of varieties Romantyka and Ustya. Increased seeding rates stimulated shortening of bean forming and seed forming periods.